Crisis Of Legal Certainty In Criminal Enforcement Against The Practice Of Repacking Food Products - Dimas Ardiansyah Sugiatno; Fenty U Puluhulawa; Weny Almoravid Dungga (Ajudikasi: Jurnal Ilmu Hukum, 2025)
The practice of repackaging food products is increasingly prevalent in Indonesia, especially in the small-business sector and in the trade of foodstuffs in small packaging without labels. This practice poses serious problems for consumer protection and food safety. Although Law No. 18 of 2012 on food has imposed a strict prohibition on opening food packaging for repackaging, this provision is subject to a normative contradiction under Article 84paragraph (2), which provides exceptions for food that is “commonly repackaged,” without clear definitions or technical limitations. This ambiguity creates a crisis of legal certainty that hinders criminal enforcement under Article 139. This study uses a socio-legal research approach, combining normative juridical analysis with empirical data from interviews with BPOM officials and field observations. The results showed that the vagueness of the norm is the main factor preventing authorities from carrying out repressive measures, thereby hindering the effective operation of criminal law enforcement. This condition has an impact on weak consumer protection, distortion of business competition, disruption of the national food security system, and potential violations of state obligations to protect the right to public Health. This study confirms the need for strict implementation regulations, repackaging technical guidelines, and strengthening BPOM capacity and consumer literacy to ensure the effectiveness of law enforcement and food safety in Indonesia.